Pengembangan Game Eduksi Berorientasi Kemampuan Berpikir Kreatif Siswa Materi Limit Fungsi Aljabar Kelas XI - Khotimah, Khusnul; Kholida, Maya (JoEMS (Journal of Education and Management Studies), 2022)
The use of media in the learning process is one of the efforts to create more meaningful and quality learning. To foster student interest in learning and improve students’ creative thinking skills, it is necessary to develop a learning media that has the concept of learning while playing so that student’ motivation in learning mathematics can increase, including by developing educational game media. The purpose of this research is to describe the development of educational games oriented to students’ creative thinking skills. The method used in this research is a development research method using the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The result obtained an average validity score of 80% with a valid category. Based on the results of student responses to educational games on the limit of algebraic function, it was concluded that at least 75% of student gave positive responses to educational games, so the educational games are practical to use and 80% of students are able to achieve learning mastery scores, so educational games are said to be effective.